The DALI study: defining antibiotic levels in intensive care unit patients: prolonged infusion of beta-lactam antibiotics in critically ill patients - Abdul Aziz, Mohd. Hafiz; Roberts, Jason A.; Akova, Murat; Basetti, Matteo; De Waele, Jan; Dimopoulos, George; Kaukonen, Maija; Koulenti, Despoina; Martin, Claude; Montravers, Paul; Rello, Jordi; Rhodes, Alan; et al. (2013)
Background – The aim of this study was to determine whether there is any pharmacokinetic and/or clinical advantage associated with the administration of beta-lactam antibiotics by prolonged infusion (PI; continuous or extended-infusion) compared to intermittent bolus (IB) dosing in critically ill patients.